GOODS DELIVERY SYSTEM APPLICATIONS IN PT. SASANA CIPTA INTERNORMA USING MICROSOFT VISUAL BASIC 5.0 - Wahyu Hidayat; Ire Puspa Wardhani, SKom, MMSI (Jurnal Sistem Informasi, 2001)
Based on research that has been done, apparently on the use of compute rized inventory PT.  INTERNORMA  SASANA CIPTA  has many advantages when compared to using manual systems. Among them are:  1. Can quickly access and enter data existing articles. 2. Can help to minimize errors in recording data items.  3. Can easily provide the required reports.